The Correlation of Salaries and Teacher Performance in Madrasah Ibtidaiyah level - Sriyadi Sriyadi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2019)
This study aims to determine whether there is a significant relationship between the honorary teacher salaries with teacher performance at MI Nurul Huda Gowak in 2019.  In this study, the population was eight honorary teachers at Madrasah Ibtidaiyah (MI) Nurul Huda Gowak, Pringsurat, Temanggung in 2019.  Because there are eight teachers, all of which will be sampled, this study is a population study.  The data was gained through questionnaires.  Data were analyzed quantitatively by Spearman correlation with SPSS 12.0 statistical software.  The result shows that there is no significant relationship between the honorary teacher salaries with teacher performance that can be known from the results of the calculation using SPSS 12.0.  The calculation using Spearman's rho obtained 0.518, while r value in Sig (2-tailed) with df 8 is 0.188. It turns out that ro (magnitude: 0.518) is greater than Sig (2-tailed) 0.188. Because ro is bigger than Sig (2-tailed), then the null hypothesis (Ho) is accepted.  It meant that there is no positive correlation between variables teacher salaries and teacher performance.  Based on this fact, it can be explained that teacher salaries have nothing to do with teacher performance.